Multi-objective design and operation of Solid Oxide Fuel Cell (SOFC) Triple Combined-cycle Power Generation systems: Integrating energy efficiency and operational safety - Sharifzadeh, Mahdi; Meghdari, Mojtaba; Rashtchian, Davood (Applied energy, 2017)
[Display omitted] •Integrating Solid Oxide Fuel Cells with thermal power plants enhance overall energy efficiency.•However, the high degree of process integration in hybrid power plants limits the operating window.•Multi-objective optimization was applied for integrated design and operation.•The Pareto optimal solutions demonstrated strong trade-off between energy efficiency and operational safety. Energy efficiency is one of the main pathways for energy security and environmental protection. In fact, the International Energy Agency asserts that without energy efficiency, 70% of targeted emission reductions are not achievable. Despite this clarity, enhancing the energy efficiency introduce significant challenge toward process operation. The reason is that the methods applied for energy-saving pose the process operation at the intersection of safety constraints. The present research aims at uncovering the trade-off between safe operation and energy efficiency; an optimization framework is developed that ensures process safety and simultaneously optimizes energy-efficiency, quantified in economic terms. The developed optimization framework is demonstrated for a solid oxide fuel cell (SOFC) power generation system. The significance of this industrial application is that SOFC power plants apply a highly degree of process integration resulting in very narrow operating windows. However, they are subject to significant uncertainties in power demand. The results demonstrate a strong trade-off between the competing objectives. It was observed that highly energy-efficient designs feature a very narrow operating window and limited flexibility. For instance, expanding the safe operating window by 100% will incur almost 47% more annualized costs. Establishing such a trade-off is essential for realizing energy-saving.